Displaying Families - Finch, Janet (Sociology, 2007)
This article argues that the sociology of contemporary family relationships should be developed to recognize the importance of ‘displaying’ as well as ‘doing’ family. The addition of the concept of ‘display’ to the sociological tool kit is not only a necessary complement to the important conceptual developments which have taken place in recent years, but is also rich in its potential for further empirical and theoretical work. In developing this theme, the article examines empirical evidence from recent UK studies of family relationships, exploring why ‘display’ is important in contemporary family relationships as well as the process through which it occurs. The article represents an initial exploration of these themes. The author's principal aim is to open up this aspect of family life for debate within the relevant sociological research community, encouraging others to refine the concept as well as to use it.
Keywords: 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; care; cours; discipline; europe; famille; hétérosexualité; maternité; postmodernisme; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; thématiques

Female Sexual Dysfunction: A Case Study of Disease Mongering and Activist Resistance - Tiefer, Leonore (PLoS Medicine, 2006)
"Tiefer highlights key steps in the ""creation"" of a new diagnosis, female sexual dysfunction, and of the campaign to challenge its reductionist approach to women's sexual problems. "
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; corps; cours; discipline; discours dominant; inégalités; patriarcat; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Prostitution et immigration des femmes latino-américaines en Espagne - Oso Casas, Laura (Cahiers du Genre, 2006)
L’objectif de cet article est de montrer qu’une bonne partie des femmes latino-américaines, contrairement à l’image souvent mise en avant de la femme objet de trafic, ont pris la décision de migrer en étant conscientes de l’activité qu’elles allaient pratiquer en Espagne. Cependant, bien qu’elles puissent opter volontairement pour le « travail » sexuel, devenant les principales pourvoyeuses économiques des foyers transnationaux (actrices de la migration, actrices économiques et du développement), elles sont prises dans plusieurs circuits qui contribuent à la reproduction des inégalités sociales. Ces circuits sont sous-tendus par l’articulation de plusieurs facteurs : la circulation des personnes, la mobilité des prostituées, la pression du foyer transnational, l’irrégularité juridique, ainsi que l’inégalité de genre.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique centrale; amérique du sud; amériques; approches et analyses; cours; discipline; espagne; europe; immigration; inégalités; migration; postmodernisme; premier cycle; prostitution; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques; travail

Le sexe des hormones : l'ambivalence fondatrice des hormones sexuelles - Sinding, Christiane (Cahiers du Genre, 2003)
Les hormones sexuelles ont été inventées à la fin du XIXe siècle comme un élixir de vie d’origine masculine. Mais ce sont les effets thérapeutiques d’autres hormones qui validèrent aux yeux de la communauté scientifique l’existence de ces nouvelles molécules. Obéissant au modèle culturel dominant de l’existence de deux sexes bien distincts, les biologistes affirmèrent qu’il existait des hormones « masculines » agissant sur les organes considérés comme masculins, et des hormones « féminines » agissant sur les caractères « féminins ». Quand on s’aperçut que les hormones masculines pouvaient avoir des effets « féminisants » sur certains organes féminins et réciproquement, on préféra mettre en doute le sexe des sujets testés plutôt que de remettre en cause le modèle binaire des sexes. Ce n’est que vers les années 1980 que certaines féministes et minorités sexuelles remirent en question le modèle biologique binaire des sexes. La pilule contraceptive fut inventée comme un outil de « libération des femmes », mais aussi de régulation des taux de naissance destiné aux pays surpeuplés et pauvres. Des hormones sexuelles sont utilisées chez des sujets sains, comme les sportifs, pour améliorer leurs performances physiques. Les hormones furent donc inventées comme agents doubles, destinés à soigner des malades, mais aussi à transformer des sujets sains.
Keywords: 1900-1999; 1980-1989; 1990-1999; approches et analyses; corps; cours; discipline; discours; discours dominant; europe; france; postmodernisme; premier cycle; procréation; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Sexualities : Sexualities and their futures - Plummer, Kenneth (Critical concepts in sociology, 2002)
Bringing together classic writings on sexuality from a social science perspective, this fascinating set covers topics including the history of the study of the area, theoretical approaches and issues of gender and sexuality. Volume four considers the wider issues around sexualities - addressing social change, postmodernity and the shifting of sexualities, and presenting an examination of the term 'queer'. An epilogue of suggested further reading is also included.
Keywords: approches et analyses; discipline; genre; postmodernisme; queer; sciences humaines; sexualité; sociologie; thématiques

Cahiers du genre: « De la contraception à l’enfantement : l’offre technologique en question » - Béland, Bibiane (Recherches féministes, 2000)
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du sud; approches et analyses; brésil; corps; corps des femmes; cours; discipline; discours dominant; droits des femmes*; europe; france; maternité; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

L’individualité féminine à l’épreuve des technologies de reproduction - Van der Ploeg (Cahiers du Genre, 1999)
Cet article décrit l’émergence de deux nouveaux types de patients, le couple et le fœtus, dans certaines techniques reproductives telles la fécondation in vitro et la chirurgie fœtale. Il montre comment l’émergence de ces patients, comme des entités traitables, est liée au développement de ces technologies. Ces pratiques médicales effacent en partie les distinctions entre le naturel et le technique, entre un individu et un autre, et sont accompagnées de dispositifs discursifs spécifiques qui rendent acceptable, voire même naturel ou inévitable le fait de traiter les problèmes de l’enfant ou de l’homme au moyen d’interventions sur le corps de la femme. Cet article est consacré à l’analyse et à la déconstruction de ces dispositifs.
Keywords: 1900-1999; 1990-1999; approches et analyses; corps; corps des femmes; cours; discipline; discours dominant; europe; france; maternité; postmodernisme; premier cycle; procréation; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Queer studies: A lesbian, gay, bisexual & transgender anthology - Beemyn, Genny; Eliason, Michele J. (New York University Press, 1996)
This book is a wide-ranging anthology which discusses the nature and diversity of queer studies, its foundations, and some of the most pressing issues in the field.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identité sexuelle; identités; identités LGBTQIA2+; philosophie politique; postmodernisme; premier cycle; queer; sciences humaines; sex3383; sexualité; sociologie; thématiques

Love and Intimacy: The Gender Division of Emotion and 'Emotion Work': A Neglected Aspect of Sociological Discussion of Heterosexual Relationships - Duncombe, Jean; Marsden, Dennis (Sociology, 1993)
This paper discusses the role of ideologies of love and intimacy in heterosexual coupledom, and examines the applicability of theories of the gender division of 'emotion work' to the field of intimate personal relationships. Research on the private sphere of the family has recently focused on quantifying instrumental aspects of relationships, such as financial management, the domestic division of labour and informal care. However, although fruitful, such approaches neglect the expressive or emotional; particularly the experiences of love and intimacy, which many people say they regard as a key element in their personal relationships. We suggest reasons for British sociology's neglect of what is almost a cliche in everyday discourse. And we present evidence (including preliminary findings from our own research on heterosexual couples) that - despite dissatisfaction with gender inequalities in domestic tasks and finance - many women express unhappiness primarily with what they perceive as men's unwillingness or incapacity to `do' the emotional intimacy which appears to them necessary to sustain close heterosexual couple relationships. We illustrate how similar discussions of gender differences in emotional behaviour have emerged elsewhere (including in the new masculinity literature), raising questions about how far men's and women's emotional behaviour can and should change.; The exploration of socially-regulated or `managed' gender divisions in intimate emotional behaviour entails two related but distinct questions: are men and women equally `susceptible' to the emotions or discourses of love and intimacy; and, do they handle such emotions in similar ways in the context of close personal relationships. We suggest how research findings on heterosexual couple relationships can be linked to work on the social regulation of emotion, which argues that there is a `gender division of emotion work' where it is assumed that women will take responsibility for the management of emotion in the private sphere.
Keywords: 1900-1999; 1980-1989; angleterre; approches et analyses; care; cours; discipline; emotional labor; europe; hétérosexualité; postmodernisme; premier cycle; périodes historiques; relations amoureuses; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; thématiques; travail